Uji Aktivitas Antioksidan Infusa Daun Strawberry (Fragaria x annanasa) Dengan Menggunakan Metode DPPH (1,1-Difenil-2-Pikrilhidrazil) - Kusuma, Ika Maruya; Djuhariah, Yayah Siti; Desi, Ika Pusma (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Antioxidant activity in strawberry leaves comes from flavonoid compounds. This study aims to determine the antioxidant activity of strawberry leaf infusion which was tested using the DPPH method. The leaves were dried, powdered, made infusion with water solvent, then tested for phytochemical screening. Then testing the antioxidant activity with the DPPH method to get the IC50 value. The results showed that strawberry leaf infusion had strong antioxidant activity with an IC50 value of 69.455 ppm and contained secondary metabolites of alkaloids, saponins, flavonoids, tannins, steroids/triterpenoids.